Optimal Relocation of Distribution Transformers using the Multiobjective Optimization Algorithm NSGA II (2014)
This paper presents a methodology for optimal relocation of transformers in distribution systems. The problem is formulated as an optimization model of multiobjective linear integer type, which considers investment and operating costs, and the benet of th